KNOWLEDGE, ATTITUDE, AND PRACTICES OF MOTHERS/CAREGIVERS ON HOME MANAGEMENT OF DIARRHEA IN CHILDREN UNDER FIVE YEARS RECEIVING CARE AT ENTEBBE HOSPITAL: A CROSS-SECTIONAL STUDY. - Samuel, Otile; Nowamani , Derrick (Student’s Journal of Health Research Africa, 2024)
Background Diarrhea is the leading killer worldwide accounting for approximately 8% of all death among under-five children despite the availability of simple effective treatment. A study in this regard was conducted to assess the knowledge, attitude, and practices of mothers/caregivers on home management of Diarrhea in children under five years. Specifically, the study sought to examine the knowledge of mothers/caregivers on home management of Diarrhea in children under five years, to assess the attitudes of mothers/caregivers on home management of Diarrhea in children under five years, and to finally determine the practices of mothers/caregivers in home management of Diarrhea in children under five years. Methods The study targeted a sample of 106 respondents (mothers/caretakers) of age group 16-50 years with children less than five years of both sexes experiencing diarrhea symptoms attending any service at Entebbe Hospital. Findings In terms of the knowledge of mothers/caregivers on home management of Diarrhea in children under five years, results from the findings indicated that of most of the respondents, 50.0% indicated unclean water as the main cause of diarrhea in children with the least indicating excessive cold. About attitudes of mothers/caretakers on home management of diarrhea in children under five years, most of the mothers (86.8%) believed that diarrhea was preventable, 12.3% of the respondents did not believe that diarrhea was preventable while 0.9% of the respondents did not know. Turning to practices of mothers/caretakers on home management of diarrhea in children under five years, most of the respondents, 44.3% indicated that they would go to a health facility when their children have diarrhea with the least, 1.9% of the respondents opting to go to a traditional herbalist. Recommendation It is therefore recommended that the government should support community sensitization programs on the diarrhea infection and their management.